Relação entre agrobiodiversidade e segurança alimentar: o caso do assentamento Vida Nova/Aragão, Miraíma-CE - Nobre, Francisca Érica Cardoso (2022)
This study has the general objective of evaluating the relationship between agrobiodiversity and food security within the families of the Vida Nova/Aragon settlement, in the municipality of Miraíma-CE. As specific objectives, it is intended to: Characterize rural families in terms of their socioeconomic and food aspects; describe the settlement in terms of agrobiodiversity indicators; measure levels of agrobiodiversity and food security; and assess the contribution of agrobiodiversity to food security. To obtain the results, a questionnaire was used with questions that included the agrobiodiversity and food security indicators. Then, agrobiodiversity and food security levels were measured and aggregated using a Likert scale ranging from 1 to 5. Finally, simple regression models were adopted, with the dependent variable being the Food Security Index (FSI) and their respective sub-indices and the independent variable was the Agrobiodiversity Condition Index (ICA). The main results indicate that the interviewees have high levels of agrobiodiversity and a medium level of food security. Among the dimensions of food security, the one that is in the best situation in the settlement is food consumption. The ISA was broken down into three dimensions: food ISA, health ISA and income ISA, with the first two having more significant results when compared to the last one. As for the contribution of agrobiodiversity to food security, the ICA had considerable impacts for both dimensions, especially when it comes to the income ISA. Thus, it is estimated that a 1% increase in ICA causes a significant average increase of 1.052% in ISA income. Therefore, the study showed the importance of agrobiodiversity to increase the food security of settled rural families.